338 Development and pilot test of an mhealth Trauma Registry in Oman. (1st September 2016) - Mehmood, Amber; Chan, Edward; Allen, Katharine; Kashmiri, Ammar Al; Busaidi, Ali Al; Stevens, Kent; Maniri, Abdullah Al; Hyder, Adnan A
Abstract : Background: Trauma registries (TRs) play a vital role in the assessment of trauma care, but are often underutilised in countries with a high burden of injuries. We postulated that emerging technologies in trauma and injury surveillance could enable the design of a tablet-based application for health care professionals. This would be used to inform trauma care and acquire surveillance data for injury control and prevention in the Sultanate of Oman. Methods: The study comprised of three steps. a) Consensus on variables to record the quality of trauma care and injury surveillance. b) Design of an electronic tablet-based application and pre-testing at the Johns Hopkins International Injury Research Unit c) Pilot study of electronic registry at two large hospitals in the Sultanate of Oman. Results: The application was designed to provide comprehensive information on each trauma case from the location of injury until discharge, so the variables were organised to cover eleven domains of information, with standardised format of data collection. Internet connexion was required only at the time of data transfer to the electronic database. Pilot study included training and induction of nurse data collectors, data collection over six months, data quality control, and data analysis. A nurse-based pilot study demonstrated that the application was user friendly, reliable, and feasible in the current setting. With approximately 2600 completed cases, the data was found to be accurate and reliable in >93% of cases. Conclusion: Initial results show the promising potential of a user-friendly, comprehensive electronic TR to develop a multicenter trauma database. The pilot test in two hospitals indicates that the registry can be used in multiple hospitals. Stakeholders engagement, training of the staff and supervised induction is the key to success and help improve injury surveillance as well as quality of trauma care.